Attitude and Practice on Foot Care among Type 2 Diabetes Mellitus Patients Attending a Tertiary Care Centre in Southern Part of Tamilnadu, India - Austoria A. J.; Aazmi M; A.R.Glannie; Liji Anna Varghese; Bismi Mohamed Ismail; Arun Pinchu Xavier (Indian Association of Preventive and Social Medicine, 2022)
Introduction : Diabetic foot has got a high prevalence of 52% among diabetics. The duration of hospital stay and physical disability are likely to cause depression and affects overall quality of life. So it is important for general population, to know about Self Care activities which include foot care practice to avert long term complications and improve quality of life which is likely to be effective in reducing the burden of diabetic foot ulcer. Objective: To assess the knowledge, attitude and practice about foot care among Type 2 DM patients in a Tertiary health care center, Tamil Nadu. Method: A cross-sectional study was done during August and September 2021 among diabetic patients after obtaining consent at a Tertiary Hospital in southern district of Tamil Nadu. Results: The mean age of the study participants was 47.56 ± 9.718 years with 55.9% being male and 44.1% female and the majority (65.6%)of subjects was residing in rural areas. Among the participants, 103 (92.8%) were found to have good attitude towards self-care activities whereas69 (62.2%) respondents practiced proper footcare. Age, gender and education were found to have significant association with the practice of proper foot care. Female gender was found to be an independent predictor for practice of adequate foot care. Conclusion: Regardless of good attitude towards diabetic foot care there is considerable resistance in practising it.